Active fault tolerant control scheme for satellite attitude system subject to actuator time‐varying faults. Issue 3 (1st February 2018) - Gao, Zhifeng; Zhou, Zepeng; Qian, Moshu S.; Lin, Jinxing
Abstract : This study investigates the active fault tolerant control (FTC) problem for the attitude system of a rigid satellite, which is affected by parameter uncertainty, unknown exogenous disturbance and actuator time‐varying faults. The upper bounds of the actuator time‐varying fault and the generalised perturbation are unknown. A novel adaptive non‐linear fault estimation observer is designed in order to obtain the estimated value of unknown time‐varying faults. Then, an active fault tolerant attitude control approach is proposed under the framework of both backstepping control and adaptive control theory. Consequently, the Lyapunov theory is used to prove the robust asymptotic stability for the closed‐loop attitude system of a faulty satellite under the proposed FTC scheme. Finally, simulation results on an in‐orbit rigid satellite are provided to show the good fault tolerant performance, which validate the effectiveness and feasibility of the proposed scheme.